Application of International association for the study of lung cancer/American Thoracic Society/European Respiratory Society criteria for the diagnosis of lung carcinomas on small biopsies: A tertiary care center experience - Balraam, K. V. Vinu; Shelly, Divya; Mishra, Prabha S.; Sampath, K. S.; Bharadwaj, Reena (South Asian Journal of Cancer, 2019)
Abstract Background: The new IASLC/ATS/ERS classification provides standardized terminology for lung cancer diagnosis in small biopsies and cytology specimens. Objectives: The aim was to study the feasibility of the guidelines using one marker for adenocarcinoma (ADC) and one for squamous cell carcinoma (SQCC) in non-small cell lung carcinomas (NSCLCs). Subject and Methods: In this study, we reviewed all the formalin-fixed paraffin-embedded tissue blocks diagnosed as lung carcinoma between July 2016 and December 2017. Cases were labeled as SCLC, ADC, SQCC, NSCLC favor ADC, NSCLC favor SQCC, NSCLC-not otherwise specified (NOS), and NSCLC-NOS possible adeno-SQCC (ADSQCC) as per IASLC/ATS/ERS 2011 guidelines. A three-step approach incorporating morphology, immunohistochemistry (IHC), and molecular analysis was used. Results: One hundred and nine cases were included. Six of the 109 cases were SCLC and 1 case was of large-cell neuroendocrine type. Of the remaining 102, 51 were diagnosed based on their classical histomorphology into SQCC (8) and ADC (43). Remaining 51 cases required IHC/special stains for categorization. The panel comprised anti-CK7, anti-thyroid transcription factor-1 (TTF-1), and anti-p63. Twenty-nine were positive for anti-TTF-1 and thus labeled as NSCLC favor ADC. Fifteen were labeled as NSCLC favor SQCC as they were highlighted by anti-p63. Four cases showed reaction to both the antibodies in different sets of tumor cells and thus were classified as NSCLC-NOS, possible ADSQCC. Remaining 3 cases did not show reaction to any of the antibodies and hence were labeled NSCLC-NOS. Conclusion: The need for every laboratory to use minimal tissue for ancillary tests to diagnose lung carcinoma on small biopsies is reemphasized. Tissue from small biopsies needs to be preserved not only for the diagnosis but also for molecular testing and evaluation of markers of resistance to therapy, in this era of personalized medicine.